(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The aim of this paper is to answer how regional sector influences higher education. These regional differences generate interest in the study of economic growth and regional development. The crucial role in spillover process is played by higher education institutions as they are the promoters of research and knowledge that stems from it. Higher education institutions should be involved in the innovation system at regional level in order to create a stimulating and competitive environment for the future growth and development. Additionally, the paper presents, compares and analyses contemporary phenomena related to the regional dimension of innovation and the role of higher education institutions in Croatia, Hungary and Slovenia. Besides teaching and research, higher education institutions must develop and emerge a “third mission” through research and technology commercialization, joint research projects, spin-off formation, mobility of researchers/teachers/students to industry and vice versa, and involvement in local and regional development projects as well. However, this is not only about knowledge spillover in some delimitated sectors, but transforming and reinvigorating the whole society on regional level. Keywords: Higher education, regional dimension of innovation, regional development